Aplikasi Gel Lidah Buaya Sebagai Edible Coating pada Daging Buah Nangka - Ansar Ansar; Sukmawaty; Guyub Mahardiawan Dwi Putra; Nurul Hafizah Najat (Jurnal Agritechno, 2020)
Jackfruit has a short shelf life, can only last between 2-3 days at room temperature. Several ways can be done to maintain the shelf life of jackfruits, such as storage in the cold room, pressurized space, or modification of the atmosphere of the room. But this method requires expensive operational costs. The purpose of this study was to examine the effect of using aloe vera gel as an edible coating to be applied to the jackfruit. The study was conducted with the stages of making aloe vera gel as an edible coating, coating the edible coating on the sample, then the sample was stored at 10 and 29oC for 10 days. The research parameters observed were water content, texture, and color. The results showed that the water content of jackfruit could be maintained using an edible coating. The shelf life of jackfruit was longer stored at 10oC than stored at 29oC. The best edible coating results obtained on the treatment of aloe vera gel with a concentration of 0.5% CMC because it can inhibit the increase in water content, maintain texture, and the color of jackfruit is still like fresh fruit. To improve the results of this study, it is necessary to conduct further research by examining the effect of aloe vera gel on the taste and aroma of jackfruit.